HUBUNGAN PERILAKU IBU TERKAIT MP-ASI STANDAR WHO DENGAN STATUS GIZI BADUTA USIA 6-23 BULAN (Studi di Kelurahan Punggawan Kota Surakarta) - Wulan Ayu Kusumanngtyas; M. Zen Rahfiludin (Jurnal Kesehatan Masyarakat (Undip), 2017)
The condition of malnutrition in infants and children is due to the inappropriate habits of breastfeeding and maternal ignorance about the benefits and ways of giving correct complementary foods so that it affects the mother's behavior in the provision of complementary foods. The aimed of this research is to analyze the relationship of mother's behavior related to WHO’s standard of complementary foods with nutritional status of age 6-23 months using weight by height indicator. The research was conducted in Punggawan, one of the sub district in Surakarta. This research was an observational analytic research with cross sectional research design. The population in this study was the mother who had child age 6-23 months in Punggawan Sub-district Surakarta amounted to 63 people. The sampling technique using purposive sampling, because there were 5 chidren who were not included in the inclusion criteria then the number of samples to 57 children. The correlation test used was Rank Spearman correlation test. The results showed that most of the mothers in Punggawan sub district were highly knowledgeable(64,9%), well behaved (80,7%) and had good actions (70,2%) related to the WHO’s standard of complementary foods and the majority of children aged 6-23 months in Punggawan sub-district had good nutritional status (87.7%). Statistical analysis showed that there was a correlation between knowledge, attitude, and action of mother related to WHO’s standard of complementary food with nutritional status of age 6-23 months (p = 0.001). It can be concluded that the mother's behavior about WHO's standard of complementary foods related to nutritional status of age 6-23 months, the better the mother's behavior the better the nutritional status of the child. Suggested further research on other factors that affect the nutritional status such as food availability, environment, sanitation and health services.